Senescent Schwann cells induced by aging and chronic denervation impair axonal regeneration following peripheral nerve injury - Andrés Flores; Cristian Gerónimo‐Olvera; Karina do Carmo de Vasconcelos Girardi; David Ñecuñir; Sandip Kumar Patel; Joanna Bons; Megan C. Wright; Daniel H. Geschwind; Ahmet Höke; Jose A. Gomez‐Sanchez; Birgit Schilling; Daniela L. Rebolledo; et al. (2023)
Abstract Following peripheral nerve injury, successful axonal growth and functional recovery require Schwann cell (SC) reprogramming into a reparative phenotype, a process dependent upon c‐Jun transcription factor activation. Unfortunately, axonal regeneration is greatly impaired in aged organisms and following chronic denervation, which can lead to poor clinical outcomes. While diminished c‐Jun expression in SCs has been associated with regenerative failure, it is unclear whether the inability to maintain a repair state is associated with the transition into an axonal growth inhibition phenotype. We here find that reparative SCs transition into a senescent phenotype, characterized by diminished c‐Jun expression and secretion of inhibitory factors for axonal regeneration in aging and chronic denervation. In both conditions, the elimination of senescent SCs by systemic senolytic drug treatment or genetic targeting improved nerve regeneration and functional recovery, increased c‐Jun expression and decreased nerve inflammation. This work provides the first characterization of senescent SCs and their influence on axonal regeneration in aging and chronic denervation, opening new avenues for enhancing regeneration and functional recovery after peripheral nerve injuries.